Interspecies interaction intensity influences water consumption in wheat–maize intercropping by regulating root length density. Issue 1 (11th November 2021) - Wang, Yifan; Yin, Wen; Hu, Falong; Fan, Zhilong; Zhao, Cai; Yu, Aizhong; Chai, Qiang
Abstract: In intercropping systems, interspecies interaction intensity has an important effect on water consumption. However, how interspecies interaction intensity reduces water consumption in intercropping is still unclear. The effects of interspecies interaction intensity in wheat ( Triticum aestivum )–maize ( Zea mays ) intercropping system on water consumption characteristics, root length density, and grain yield were examined. A 3‐yr field experiment was conducted to evaluate three root interaction intensities: complete belowground interaction (W/M, without root barrier), partial belowground interaction (NW/M, nylon mesh barrier), and without belowground interaction (PW/M, plastic sheet barrier), with two plant densities of maize (45, 000 plants ha −1, M1, and 52, 500 plants ha −1, M2) in wheat–maize intercropping system. During co‐growth period of wheat and maize and independent growth of maize, evaporation was reduced by W/M and with increased maize plant density. Root length density of maize was inhibited by intercropped wheat during the co‐growth period. Root length density of maize in the W/M treatment was increased by 14% in 2014 and 45% in 2015, compared with the NW/M treatment, and increased by 26% in 2014 and 119% in 2015, compared with the PW/M treatment, expect for 2016, during maize independent growth. Moreover, there was a negative correlation between evaporation and root length density of maize. Grain yield was increased by W/M2 treatment. Increasing interspecies interaction intensity can decrease evaporation by increasing the root length density of intercropping crops. Core Ideas: With increased maize plant density, evaporation was reduced by complete belowground interaction. Root length density of maize was increased by complete belowground interaction. Root length density of maize was negatively correlated with evaporation.